2007
DOI: 10.1016/j.cdp.2007.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of cell proliferation, induction of apoptosis, reactivation of DLC1, and modulation of other gene expression by dietary flavone in breast cancer cell lines

Abstract: Background-Dietary flavone was previously shown to increase the expression of deleted in liver cancer-1 gene (DLC-1) in HT-29 colon carcinoma cell line (Proteomics 2004;4:2455-64). DLC-1 that encodes a Rho GTPase-activating protein, functions as a tumor suppressor gene and is frequently inactivated or down-regulated in several common cancers. Restoration of DLC-1 expression suppresses in vitro tumor cells proliferation and tumorigenicity in vivo.Methods-Here, the effect of flavone was examined in several DLC-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 43 publications
2
32
0
Order By: Relevance
“…The potential treatment and prevention effects have been shown in degenerative diseases such as tumors, aging and cardiovascular diseases [10][11][12][13][14][15]. Additionally, some compounds of flavonoids possess potential application prospects as weak hormones at treating menopausal syndrome of women [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The potential treatment and prevention effects have been shown in degenerative diseases such as tumors, aging and cardiovascular diseases [10][11][12][13][14][15]. Additionally, some compounds of flavonoids possess potential application prospects as weak hormones at treating menopausal syndrome of women [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The proliferation and apoptosis of tumour cells consist of a precise process regulated by multiple genes. Many studies both at home and abroad have demonstrated that flavonoid compounds can inhibit the proliferation of tumour cells, induce the apoptosis of tumour cells and regulate the expression of relevant genes to block the occurrence and development of tumour cells (12)(13)(14)(15). Isoquercitrin, the effective monomer from Bidens bipinnata L. extract, was used in the present study.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Loss of DLC1 expression, due to chromosomal deletion or promoter hypermethylation, has been detected in 50% of human hepatocellular carcinomas, and in many other human malignancies, including breast, prostate, colon, and lung. [10][11][12][13] Accordingly, therapeutic upregulation of DLC1 expression in cancer cells has been proposed as a novel method to induce apoptosis, and inhibit cell proliferation and colony formation, 14,15 and to restrain cell migration and suppress metastasis. [16][17][18] A key factor in the phosphatidylinositol-3-kinase (PI3K)/AKT signaling pathway is PIK3CA.…”
mentioning
confidence: 99%